Connecting vascular aging and frailty in Alzheimer's disease. (April 2021) - Sabbatinelli, Jacopo; Ramini, Deborah; Giuliani, Angelica; Recchioni, Rina; Spazzafumo, Liana; Olivieri, Fabiola
Highlights: Inflammaging is a key contributor to Alzheimer's disease (AD) pathophysiology. Most of the cellular and molecular mechanisms of aging are involved in the AD-related vascular dysfunction. Early cardiovascular interventions modulate the trajectory of age-related cognitive decline. Understanding the connection between dementia, frailty, and cardiovascular disease is crucial in the prevention of AD. Abstract: Aging plays an important role in the etiology of the most common age-related diseases (ARDs), including Alzheimer's disease (AD). The increasing number of AD patients and the lack of disease-modifying drugs warranted intensive research to tackle the pathophysiological mechanisms underpinning AD development. Vascular aging/dysfunction is a common feature of almost all ARDs, including cardiovascular (CV) diseases, diabetes and AD. To this regard, interventions aimed at modifying CV outcomes are under extensive investigation for their pleiotropic role in ameliorating and slowing down cognitive impairment in middle-life and elderly individuals. Evidence from observational and clinical studies confirm the notion that the earlier the interventions are conducted, the most favorable are the effects on cognitive function. Therefore, epidemiological research should focus on the early detection of deviations from a healthy cognitive aging trajectory, through the stratification of adult individuals according to the rate of aging. Here, we review the interplay between vascular and cognitive dysfunctions associated with aging, to disentangle the complex mechanisms underpinning the development and progression of neurodegenerative disorders, with a specific focus on AD.